Pengaruh Pengunaan Media Peta Dan Atlas Dalam Meningkatkan Literasi Spasial Siswa Pada Pembelajaran Abad 21 - Mutiara Dwi Putri; Elfia Sukma (CV. ITTC INDONESIA, 2026)
The transformation of 21st-century education requires students to possess skills that enable them to think critically and understand information effectively. One of these essential skills is spatial literacy. Spatial literacy helps students understand spatial concepts such as location, direction, distance, and interregional relationships, which are commonly discussed in Social Studies learning. However, spatial materials are often considered difficult by students because they tend to be presented in an abstract manner. This study aims to examine the effect of using maps and atlases as learning media on students' spatial literacy skills by reviewing relevant scientific references. The study employed a literature review method by analyzing various sources, including journals, books, scientific articles, and previous research related to maps, atlases, and spatial literacy skills. Data were collected through the review and analysis of relevant written sources and literature. The findings indicate that the use of maps and atlases has a positive effect on improving students' spatial literacy skills. After using these media in the learning process, students demonstrated better abilities in understanding spatial information, identifying locations, recognizing directions, and explaining relationships between regions. Therefore, maps and atlases can be used as effective learning media to support Social Studies education in the era of 21st-century learning.